Flagellin Modulates the Function of Invariant NKT Cells From Patients With Asthma via Dendritic Cells - Shim, Jae-Uoong; Rhee, Joon-Haeng; Jeong, Ji-Ung; Koh, Young-Il (Allergy, asthma & immunology research, 2016)
Invariant natural killer T (iNKT) cells play a critical role in the pathogenesis of asthma. We previously reported the association between circulating Th2-like iNKT cells and lung function in asthma patients and the suppressive effect of Toll-like receptor 5 ligand flagellin B (FlaB) on asthmatic in a mouse model. Thus, we investigated whether FlaB modulates the function of circulating iNKT cells in asthmatic patients. Peripheral blood mononuclear cells (PBMCs) were treated with FlaB, and the secreted and intracellular cytokines of iNKT cells were evaluated by using ELISA and flow cytometry, respectively, following stimulation with α-galactosylceramide. Foxp3⁺ iNKT cells were also measured. To determine the effect of FlaB-treated dendritic cells (DCs) on iNKT cells, we co-cultured CD14⁺ monocyte-derived DCs and T cells from patients with house dust mite-sensitive asthma and analyzed intracellular cytokines in iNKT cells. A reduction of IL-4 and IL-17 production by iNKT cells in PBMCs after FlaB treatment was alleviated following blocking of IL-10 signaling. A decrease in the frequencies of IL-4⁺ and IL-17⁺ iNKT cells by FlaB-treated DCs was reversed after blocking of IL-10 signaling. Simultaneously, an increase in Foxp3⁺ iNKT cells induced by FlaB treatment disappeared after blocking of IL-10. FlaB may inhibit Th2- and Th17-like iNKT cells and induce Foxp3⁺ iNKT cells by DCs via an IL-10-dependent mechanism in asthmatic patients. In patients with a specific asthma phenotype associated with iNKT cells, FlaB may be an effective immunomodulator for iNKT cell-targeted immunotherapy.